2019
DOI: 10.35315/dinamik.v24i1.7835
|View full text |Cite
|
Sign up to set email alerts
|

Standar Operasional Dan Prosedur Perangkat Bantu Elektronik Kumbung Jamur

Abstract: Pengelolaan jamur tiram memang masih memiliki komoditas andalan bagi peningkatan ekonomi masyarakat. Namun beragam kendala telah menghadapkan petani pembudidaya dengan berbagai upaya penerapan teknologi kekinian. Salah satunya adalah pengendalian dan pengelolaan area kumbung jamur dengan pengaturan teknologi elektronik. Perlunya penerapan standar operasional dan prosedur guna mendukung penerapan teknologi ini sebagai salah satu upaya pendekatan kondisi alamiah diharapkan akan memberikan dampak yang signifikan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…That is related to agricultural typical such as perishable products, so according to Yuantari et al [16] the marketing dimension is critical to fulfilling consumer requirements (quality, quantity and time delivery). According to Sukur and Soesanto [17] nowadays, the smartphone has been using widely, including by farmers. This fact showed that the rural development is reliable to bedone in the rural zone.…”
Section: Determining Of Weight Importance External Aspectmentioning
confidence: 99%
“…That is related to agricultural typical such as perishable products, so according to Yuantari et al [16] the marketing dimension is critical to fulfilling consumer requirements (quality, quantity and time delivery). According to Sukur and Soesanto [17] nowadays, the smartphone has been using widely, including by farmers. This fact showed that the rural development is reliable to bedone in the rural zone.…”
Section: Determining Of Weight Importance External Aspectmentioning
confidence: 99%